Optimering av stakning i längdskidåkningens klassiska stil - Hartung, I.; Sjoestroem, J. (2000)
This paper is about how to build a virtual skier, to simulate a double-poling movement in the classic style of cross-country skiing and optimize it. The model has been limited to include only upperbody, arm, hand and a ski pole. The skier is 160 cm tall and weights 60 kg. A software called AnyBody, which still is under construction, has been the tool to receive the results. A primer goal during this work has been to minimize the metabolic energy during the movement but also to calculate an optimal ski-pole length. The muscles included in the model have been approximated to be linear between two points. The anthropometric data of muscles, which is available today, is very insufficient so many values have been assumed to fit the model. When calculating the optimal ski-pole length the metabolic energy has been used as the costfunction. It was minimized with constant velocity. The original model consumed 1659 J in metabolic energy while producing 168 W in mechanical power. After optimization the metabolic energy reduced 29 % to 1165 J at unchanged mechanical muscle power. The ski-pole length decreased from 135 to 134 cm. Due to all limitations while constructing the model, the results can not be considered realistic. The virtual model has to be completed with the whole body and all muscles to be total valid. The interesting of this paper is the procedure to the result and the future opportunities in the subject.